2015
DOI: 10.1016/j.nicl.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Network analysis of EEG related functional MRI changes due to medication withdrawal in focal epilepsy

Abstract: Anti-epileptic drugs (AEDs) have a global effect on the neurophysiology of the brain which is most likely reflected in functional brain activity recorded with EEG and fMRI. These effects may cause substantial inter-subject variability in studies where EEG correlated functional MRI (EEG–fMRI) is used to determine the epileptogenic zone in patients who are candidate for epilepsy surgery. In the present study the effects on resting state fMRI are quantified in conditions with AED administration and after withdraw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
(59 reference statements)
1
13
0
Order By: Relevance
“…FC maps could be influenced by AEDs and other clinical factors (i.e., cognitive impairment). In our case, AEDs were too heterogeneous to be studied in detail . Nevertheless, our analysis focused on the effect of IEDs on connectivity maps seeded from the presumed EZ.…”
Section: Discussionmentioning
confidence: 97%
“…FC maps could be influenced by AEDs and other clinical factors (i.e., cognitive impairment). In our case, AEDs were too heterogeneous to be studied in detail . Nevertheless, our analysis focused on the effect of IEDs on connectivity maps seeded from the presumed EZ.…”
Section: Discussionmentioning
confidence: 97%
“…Withdrawing antiepileptic medications during inpatient EEG‐video monitoring enables this step to be taken safely in a medically supervised environment (considering the risk of provoking frequent or prolonged seizures) and allows these medication‐reduced EEG‐fMRI studies to be performed without ethical concerns . Organizing such studies at short notice can be a logistical challenge, due to MR scanner unavailability and timely MRI safety clearance. This can be overcome by the weekly scheduled timeslot for inpatient EEG‐fMRI studies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous studies have explored the influence of AEDs on functional connectivity, and found a significant correlation [Hermans et al, 2015]. Therefore, it would be interesting for future analyses to determine the interaction between medication, IEDs and the subsequent effect on connectivity.…”
Section: Transient and Non-transient Effects Of Iedsmentioning
confidence: 99%